1996
DOI: 10.1111/j.1365-2672.1996.tb03524.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid metabolism under different glucose concentrations of Leuconostoc oenos from wine

Abstract: F.M. SAGUIR AND M.C. MANCA DE NADRA. 1996. Leirconostor oenos M isolated from wine did not grow in the absence of glucose and it was clearly stimulated by the presence of ~.-malic and citric acids in synthetic medium with different glucose concentrations. In basal medium, D-glucose and L-malic and citric acids were simultaneously consumed. I,-Malic acid was metabolized at a higher rate than glucose and citric acid. When the organic acids were completely consumed only 50% of the glucose was utilized. In basal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
5
12
0
Order By: Relevance
“…The results suggested that another factor apart from the substrate availability became growth limiting, perhaps the inhibition of end‐products when glucose was more than a concentration of 5 g l −1 . This was in agreement with the observation of Saguir and Manca de Nadra (1996).…”
Section: Resultssupporting
confidence: 94%
“…The results suggested that another factor apart from the substrate availability became growth limiting, perhaps the inhibition of end‐products when glucose was more than a concentration of 5 g l −1 . This was in agreement with the observation of Saguir and Manca de Nadra (1996).…”
Section: Resultssupporting
confidence: 94%
“…l-malic acid increased both growth parameters of about 13% and 36%, respectively. Similar results were observed by Saguir and Manca de Nadra 11,27 and Aredes Fernandez and colleagues. 28 When the initial pH was adjusted at 3.8, growth rate and final biomass of the MS25 strain significantly decreased.…”
Section: Effect Of Ph and L-malic Acid On Growth And Carbon Source Utsupporting
confidence: 89%
“…An interesting finding was that the highest proportion of O. oeni population (61%) did not possess the capacity to produce diacetyl, acetoin, and 2,3-butilenglycol, contrary to that observed for β-glucosidase activty. Saguir and Manca de Nadra 9,27 reported that in one O. oeni strain from wine, that no diacetyl, acetoin, 2,3-butilenglycol were found during growing in a complete or n-deficient synthetic media. In our study no direct relation among the O. oeni isolates for both biochemical activities could be clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of L-malic acid in the culture medium, especially in the concentrations of 2 and 4 g/L, slightly stimulated the growth of the three strains as expressed by the final biomasses obtained (data not shown). The stimulatory effect of malic acid on the growth of wine LAB, such as O. oeni, is well documented (Firme et al, 1994;Kunkee, 1991;Loubiere et al, 1992;Saguir and Manca de Nadra, 1996). Henick-Kling (1989, 1995) were able to demonstrate, based on the chemiosmotic theory, the biochemical benefit of malolactic fermentation, as an ATP yielding process.…”
Section: Effect Of L-malic Acid On the Production Of Volatile Phenolsmentioning
confidence: 98%